Contribution of CSR assurance quality to the market valuation of voluntary standalone reports: An investigation of the French context - Nekhili, Mehdi; Lajmi, Amira; Nagati, Haithem; Paché, Gilles (Management international / International Management / Gestiòn Internacional, 2022)
This paper investigates the moderating role of quality of assurance services, focusing on their scope, level of application, and the choice of a professional auditor as assurance provider. The study also explores the relationship between the issuance of a standalone corporate social responsibility (CSR) report and a firm’s market value (as measured by Tobin’s q). The econometric analysis is based on a matched sample of large French firms listed in the SBF 120 index between 2007 and 2017. The findings indicate that the relationship between the issuance of a standalone CSR report and Tobin’s q is negative but becomes positive when firms use higher-quality assurance services.